Go-6976 reverses hyperglycemia-induced insulin resistance independently of cPKC inhibition in adipocytes. - Katherine A Robinson; Krisztina Hegyi; Yusuf A Hannun; Maria G Buse; Jaswinder K Sethi (PLoS ONE)
Chronic hyperglycemia induces insulin resistance by mechanisms that are incompletely understood. One model of hyperglycemia-induced insulin resistance involves chronic preincubation of adipocytes in the presence of high glucose and low insulin concentrations. We have previously shown that the mTOR complex 1 (mTORC1) plays a partial role in the development of insulin resistance in this model. Here, we demonstrate that treatment with Go-6976, a widely used "specific" inhibitor of cPKCs, alleviates hyperglycemia-induced insulin resistance. However, the effects of mTOR inhibitor, rapamycin and Go-6976 were not additive and only rapamycin restored impaired insulin-stimulated AKT activation. Although, PKCα, (but not -β) was abundantly expressed in these adipocytes, our studies indicate cPKCs do not play a major role in causing insulin-resistance in this model. There was no evidence of changes in the expression or phosphorylation of PKCα, and PKCα knock-down did not prevent the reduction of insulin-stimulated glucose transport. This was also consistent with lack of IRS-1 phosphorylation on Ser-24 in hyperglycemia-induced insulin-resistant adipocytes. Treatment with Go-6976 did inhibit a component of the mTORC1 pathway, as evidenced by decreased phosphorylation of S6 ribosomal protein. Raptor knock-down enhanced the effect of insulin on glucose transport in insulin resistant adipocytes. Go-6976 had the same effect in control cells, but was ineffective in cells with Raptor knock-down. Taken together these findings suggest that Go-6976 exerts its effect in alleviating hyperglycemia-induced insulin-resistance independently of cPKC inhibition and may target components of the mTORC1 signaling pathway.